2008
DOI: 10.1002/jssc.200800117
|View full text |Cite
|
Sign up to set email alerts
|

An accurate and nondestructive GC method for determination of cocaine on US paper currency

Abstract: The presence of cocaine on US paper currency has been known for a long time. Banknotes become contaminated during the exchange, storage, and abuse of cocaine. The analysis of cocaine on various denominations of US banknotes in the general circulation can provide law enforcement circles and forensic epidemiologists objective and timely information on epidemiology of illicit drug use and on how to differentiate money contaminated in the general circulation from banknotes used in drug transaction. A simple, nonde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…Our findings agree with previously published studies (6–12) in that cocaine is one of the most extensively abused illicit drugs in the world, and that most of the paper currency in general circulation is contaminated with cocaine (8). As previously cited, Spain has had the highest abuse rates for cocaine in Europe for the last decade and rates higher than U.S.A. in recent years (2).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings agree with previously published studies (6–12) in that cocaine is one of the most extensively abused illicit drugs in the world, and that most of the paper currency in general circulation is contaminated with cocaine (8). As previously cited, Spain has had the highest abuse rates for cocaine in Europe for the last decade and rates higher than U.S.A. in recent years (2).…”
Section: Discussionsupporting
confidence: 93%
“…Zuo et al also demonstrated another novel way to monitor drug use, in which GC-MS was employed to detect cocaine on US paper currency [26]. These studies together with other similar ones indicated that development of methods based on modern analytical chemistry could be a new trend in drug use monitoring.…”
Section: Discussionmentioning
confidence: 91%
“…This can occur if the individual is present in an environment where the drugs are being consumed (e.g., smoked drugs) or accidentally rubs the hair with contaminated or dirty hands. For example, cocaine and cannabis have been detected in currency banknotes [119,120]. Those drugs are actually the most [24] 0.13 ng/ml; 0.…”
Section: Cocaine Determination In Hairmentioning
confidence: 99%